1984
DOI: 10.1159/000260808
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Glucose Clearance after Rinsing with Solutions of Different Concentrations of Glucose

Abstract: The rate of salivary glucose clearance was determined in 6 subjects after rinsing with solutions ranging in concentration from 0.3 to 50%. 6 repeated rinses of 10% glucose by 1 subject gave clearance times, i.e. time to reach 10 mg%, ranging from 18.7 to 24.6 min, while the clearance time of single rinses by each of the subjects ranged from 13.6 to 23.3 min. The coefficients of variation were 9.8 and 21.7%. Plotting the logarithm of the saliva concentrations of glucose against time gave linear curves (r close … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

1986
1986
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 3 publications
1
24
0
Order By: Relevance
“…Lanke [1957] reported that there tended to be greater variation in food retention between individuals eating the same food than within individuals eating different foods. These con clusions have been repeated by other authors, such as Sundstrôm and Ericsson [1968] and Goulet and Brudevold [1984], Kashket et al [ 1991 ] reported that consumers are ve ry poor at predicting which foods are more retentive in the oral cavity. Their results agreed with those of Bibby et al [1986], who concluded that foods with a higher sucrose con tent cleared more quickly.…”
supporting
confidence: 60%
See 1 more Smart Citation
“…Lanke [1957] reported that there tended to be greater variation in food retention between individuals eating the same food than within individuals eating different foods. These con clusions have been repeated by other authors, such as Sundstrôm and Ericsson [1968] and Goulet and Brudevold [1984], Kashket et al [ 1991 ] reported that consumers are ve ry poor at predicting which foods are more retentive in the oral cavity. Their results agreed with those of Bibby et al [1986], who concluded that foods with a higher sucrose con tent cleared more quickly.…”
supporting
confidence: 60%
“…1957;Sundstrom and Ericsson. 1968;Goulet and Brudevold, 1984], The more retentive foods, such as white bread, wholemeal bread and rice were also associated with a greater and longer pi I drop as mea sured by the indwelling electrode with telemetry. This il lustrates the influence of food retention on cariogenic po tential.…”
Section: Acidogcnicity and Salivary Carbohydrate Content After Eatingmentioning
confidence: 99%
“…A likely prerequisite for such an influence is that the clearance process does not vary substantially in an individual over extended periods of time and that the clearance process differs among individuals. It has been suggested that the rate at which substances are cleared from the oral cavity is a characteristic of individual subjects reflecting inter-subject variability in susceptibility to caries [Swenander Lanke, 1957;Sundstrom and Ericsson, 1968;Adorjan and Stack, 1976;Goulet and Brudevold, 1984;Goulet ct al., 1985;Wcathercll et al, 1986;Wennerholm et al, 1986], In none of these studies was the intra individual variability of oral sucrose clearance followed over a long time period. The aim of the present study was to follow the individual clearance process over a long period of time in order to eval uate inter-and intra-individual differences.…”
mentioning
confidence: 99%
“…This new finding may reflect the higher sensitivity of the carbohydrate assay system used and that fluoride was added to all samples immediately on collection as an inhibitor of glycolysis. The finding that glucose levels after 60 min were approximately the same despite the high glucose content of the chocolate bar is at variance with Goulet and Brudevold [1984]. They found the rate of glucose clearance decreased with increase in the level of glucose, albeit in rinse solutions.…”
Section: Discussionmentioning
confidence: 93%
“…Since cariogenic effects are, in part, related to the retention time of carbohydrates in the mouth as a result of their acidogenicity, the role of saliva in oral carbohydrate clearance is of primary interest. The salivary clearance of sugars is influenced by the properties of the foodstuff [Lundqvist, 1952], the amount of ingested carbohydrate [Goulet and Brudevold, 1984], the sampling site in the mouth [Britse and Lagerlöf, 1987;Strong et al, 1987] and physiological factors such as salivary flow rate and the volume of saliva in the mouth before and after swallowing [Dawes, 1983;Lagerlöf et al, 1987].…”
mentioning
confidence: 99%